Protein sensors and reactive oxygen species / B Thiol enzymes and proteins - Sies, Helmut; Packer, Lester (Protein sensors and reactive oxygen species, 2002)
This volume of Methods in Enzymology is a companion to Volume 347 and addresses direct sensing of reactive oxygen species and related free radicals by thiol enzymes and proteins